Application of the SOS/umu test and high‐content in vitro micronucleus test to determine genotoxicity and cytotoxicity of nine benzothiazoles. Issue 12 (30th January 2014) - Ye, Yan; Weiwei, Jiang; Na, Li; Mei, Ma; Kaifeng, Rao; Zijian, Wang
ABSTRACT Benzothiazole and benzothiazole derivatives (BTs) have been detected in various environmental matrices as well as in human beings, but little is currently available regarding their toxicities. In our study, genotoxicities of nine BTs (benzothiazole [BT], 2‐chlorobenzothiazole [CBT], 2‐bromobenzothiazole [BrBT], 2‐fluorobenzothiazole [FBT], 2‐methylbenzothiazole [MeBT], 2‐mercaptobenzothiazole [MBT], 2‐aminobenzothiazole [ABT], 2‐hydroxy‐benzothiazole [OHBT] and 2‐methythiobenzothiazole [MTBT]) are comprehensively evaluated by the SOS/umu test using the bacterial Salmonella typhimurium TA1535/pSK1002 for DNA‐damaging effect and the high content in vitro micronucleus test using two human carcinoma cells (MGC‐803 and A549) for chromosome‐damaging effect. The cytotoxicity of BTs on both bacteria and two human cells was also evaluated. Except for the cytotoxic effect of MBT on MGC‐803 and A549, the other tested BTs showed more than 50% cytotoxicity at their highest concentrations in a dose‐dependent manner, and their LC50s ranged from 19 (MBT in bacteria) to 270 mg l–1 (CBT in A549). Activation and inactivation were observed for specific BTs after metabolism. On the other hand, no evidence of genotoxicity was obtained for BT, FBT and MBT, and DNA damage was induced by ABT, OHBT, BrBT and MTBT in MGC‐803, by MeBT in A549 and by CBT in both cells. Through quantitative structure–activity relationship analysis, two structure alerts for chemical genotoxicity, including heterocyclic amine and hacceptor‐path3‐hacceptor are present in ABT and OHBT respectively; however, the underlying mechanisms still need further evaluation. Copyright © 2014 John Wiley & Sons, Ltd.